Optimalisasi Fungsi Legislasi Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Halmahera Utara dalam Pembentukan Peraturan Daerah - Uang, Yulinda; Tjuluku, Selvi (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to determine and analyze the implementation of the role of the regional government in this case the Regional People's Representative Council (DPRD) and the executive of North Halmahera Regency optimally in carrying out the task of forming regional regulations starting from planning, drafting regional regulations, discussions to stipulation or ratification and promulgation in the regional gazette. This study is a qualitative descriptive study, namely research that aims to describe and describe events or phenomena that occur in the field and present data systematically, factually and accurately regarding the facts or phenomena that occur in the field. The results of the study indicate that, 1). The portrait of the availability of human resources spread across each Regional Apparatus Organization (OPD) and the Secretariat of the DPRD of North Halmahera Regency in preparing draft regional regulations has very low educational qualifications and HR experience due to the lack of technical guidance and training on technical, mechanisms, norms and mastery of the substance of draft regional regulations in each field; 2). The availability of supporting facilities and infrastructure at the Secretariat of the DPRD of North Halmahera Regency is sufficient in terms of quantity, but its utilization has not been maximized because some are in repair status due to minor and severe damage and in particular the availability of official cars for members of the DPRD of North Halmahera Regency is not evenly distributed; 3). The SOP for the formation of regional regulations in North Halmahera Regency is available, but the flow and mechanisms contained therein are not in accordance with applicable regulations, resulting in the quality of the regulations formed being relatively low and not in accordance with the expected time target; 4). Accountability for the process of forming regional regulations by the DPRD and the Executive of North Halmahera Regency vertically in the form of routine accountability reports is carried out, but often experiences delays, while measuring the level of effectiveness of the implementation of regional regulations that have been formed as a form of horizontal accountability of the DPRD and the Executive of North Halmahera Regency to the public has not been carried out because there is no instrument that has been made and used to measure the level of accountability.